(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Diabetes mellitus represents one of the most significant global public health challenges due to its increasing prevalence, chronic course, and association with severe complications. This study aims to assess modern diagnostic approaches and preventive strategies for diabetes mellitus within the framework of evidence-based medicine. The analysis is based on contemporary clinical guidelines, systematic reviews, and large-scale clinical studies evaluating the effectiveness and diagnostic accuracy of current screening tools and preventive interventions. Particular attention is given to the role of laboratory biomarkers, risk stratification models, and non-invasive diagnostic methods in the early detection of diabetes, as well as lifestyle modification, pharmacological prevention, and population-based interventions supported by high-level evidence. The findings indicate that the application of evidence-based diagnostic algorithms enables earlier identification of individuals at high risk, while preventive strategies grounded in robust clinical evidence significantly reduce diabetes incidence and delay disease progression. The results emphasize that integrating modern diagnostic technologies with evidence-based preventive measures is essential for improving diabetes control and reducing long-term health and economic burdens.